Determinan Keberlanjutan Usaha Coffee Shop: Mediasi Keunggulan Kompetitif - Verga Aulia Putri; Yuhendri Leo Vrista (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2026)
The objective of this study is to analyze the effects of Product Innovation, Market Orientation, and Social Media Utilization on Business Sustainability, with Competitive Advantage as a mediating variable in coffee shop businesses in Padang City. The study was motivated by increasing competition among coffee shops and the challenges of maintaining long-term Business Sustainability. A causal research design was used in conjunction with a quantitative technique. Data were collected by distributing questionnaires to 180 coffee shop business actors in Padang City and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings indicate that Product Innovation (β = 0.395; p < 0.001), Market Orientation (β = 0.397; p < 0.001), and Social Media Utilization (β = 0.260; p < 0.001) significantly affect Competitive Advantage. Furthermore, Market Orientation (β = 0.229; p = 0.002) and Competitive Advantage (β = 0.599; p < 0.001) significantly affect Business Sustainability, whereas Product Innovation (β = -0.013; p = 0.859) and Social Media Utilization (β = 0.090; p = 0.125) do not have a direct significant effect on Business Sustainability. The results also indicate that the relationships between Product Innovation, Market Orientation, Social Media Utilization, and Business Sustainability are mediated by Competitive Advantage. These findings highlight the importance of strengthening Competitive Advantage through innovation, market responsiveness, and effective Social Media Utilization to support long-term Business Sustainability.